Análise das propriedades antioxidantes das oximas 3-(fenil hidrazona) butano-2-ona e butano-2,3-dionatiosemicarbazona - Puntel, Gustavo Orione (2008)
Oximes are chemical compounds used to reactivate the inhibited acetylcholinesterase (AChE) enzyme by organophosphates (OPs). The OPs, besides classically recognized as AChE irreversible inhibitors, are also involved in the generation of oxidative stress conditions. However, researches focusing on the possible antioxidant properties of oximes are lacking in the literature. The aim of this study was to investigate the potential antioxidant and toxic properties of 3-(phenylhydrazono)butan-2-one oxime and butane-2,3-dionethiosemicarbazone oxime in mice, and to understand the mechanism(s) by which they act. Firstly, we investigated the existence and the mechanism(s) by which 3- (phenylhydrazono)butan-2-one oxime exert its antioxidant properties (Manuscript 1). The obtained results show that in vitro hydrogen peroxide (H2O2), malonate, or ferrous ions (Fe2+)-induced lipid peroxidation was decreased by low concentrations of the oxime. Oxime treatment did not modify the basal peroxidation level nor prevented the induced lipid peroxidation determined ex vivo. The obtained results suggest that 3-(phenylhydrazono)butan-2-one oxime could be employed as a satisfactory antioxidant compound. The absence of toxicity signs after in vivo administration of 3-(phenylhydrazono)butan-2-one oxime to mice may indicate that it could be a safe drug for further studies. The other objective of this study was to investigate the existence and the mechanism(s) by which butane-2,3-dionethiosemicarbazone oxime exert its antioxidant properties (Manuscript 2). The obtained results indicate a significant H2O2, nitric oxide (NO) and 1,1-diphenyl-2-picrylhydrazyl (DPPH●) scavenging activity at low oxime concentrations. Besides, the butane-2,3-dionethiosemicarbazone oxime significantly diminished the deoxyribose degradation induced by Fe2+ or Fe2+ + H2O2, and also the benzoate hydroxylation induced by ferric ions (Fe3+) + H2O2 reaction. Besides, the oxime showed a significant inhibitory effect on s-phenantroline reaction with Fe2+. A significant decrease in the basal and pro-oxidants induced lipid peroxidation in brain, liver, and kidney of mice was observed both in vitro and ex vivo. In addition, in our ex vivo experiments the butane-2,3- dionethiosemicarbazone oxime did not determine significant changes in thiol (-SH) levels of liver, kidney and brain, as well as did not modify the delta-aminolevulinate dehydratase (δ- ALA-D) activity in these tissues of mice. The obtained results indicate that the oximes tested depicted significant antioxidant properties, and that further studies are necessary to improve our knowledge regarding the exact antioxidant action mechanism of these oximes.